A gaping gap (smokeless tobacco control in Pakistan). Issue 1 (December 2016) - Khan, Zohaib
Abstract Oral cancer is second most common cancer in Pakistan and one of the major contributing factors to its high incidence is smokeless tobacco (SLT) use. 5.3% of Pakistan's youth are current SLT users. The World Health Organization requires the signatories of its "Framework Convention on Tobacco Control" to officially ban the sale of tobacco products to minors. We reviewed the Government of Pakistan's tobacco control, and related supporting policies, to assess how these address the issue of sale of SLT products to minors and found evident gaps in this regard. Legislations need to be in place to ban the sale of SLT products to minors and avoid an SLT epidemic in the future.